PSYCHOSOCIAL DEVELOPMENT OF THE CHILDREN - Scania Riendravi (Universitas Udayana, 2013)
Family have an important role as a basic of emotional and social development. Friendships also influence the psychosocial development of the children. Psychosocial development of children will be improved with changes in their knowledge and understanding of the needs and regulations. Understand the psychosocial development of the children will help the parents and teachers educate their childrens / students and optimize the process of development in a proper way.